The Transformation from Spiritual to Managerial Leadership: A Study of Changes in Organizational Governance at Traditional Educational Institutions Toward ISO Standards - Abdul Rohman; M. Ilham Ainun Najib; Ainur Rofiq (Global Education Journal, 2026)
The transformation of leadership from spiritual to managerial is not merely a change in organizational structure. This study aims to analyze the process of transformation from spiritual leadership to managerial leadership in the organizational governance reform of a traditional educational institution toward the implementation of ISO standards at MTs Darussalam Blokagung, Banyuwangi. This study employs a qualitative approach using a case study design to analyze the transformation from spiritual leadership to managerial leadership in the shift in organizational governance toward the implementation of ISO standards at MTs Darussalam Blokagung in Banyuwangi. Data were collected through non-participant observation, semi-structured interviews with four purposively selected informants, and document analysis. Data analysis utilized the interactive model by Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and drawing conclusions. Data validity was ensured through source triangulation, methodological triangulation, member checking, and peer debriefing. The research results indicate that the leadership transformation at MTs Darussalam Blokagung Banyuwangi toward the implementation of ISO standards occurred through the integration of spiritual values into a modern organizational governance system.